Strategi Pedagang UMKM Hadapi Inflasi: Analisis Ekonomi Manajerial & SWOT - Dian Saputri; Risma Nurul Fadilah; Ratu Syahlaa’ Qurrotu‘Ainii; Pupung Purnamasari (GLOBAL SCIENTS PUBLISHER, 2025)
In the dynamic modern economy, inflation poses a significant challenge for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, which serve as the backbone of the national economy. This research focuses on analyzing the strategies employed by MSMEs, specifically Kedai AA in Cikarang, in confronting raw material price fluctuations caused by inflation. The primary objective is to comprehend the application of managerial economic strategies and SWOT analysis for business sustainability amidst these economic pressures. Employing a qualitative approach with a case study methodology, data was meticulously collected through in-depth interviews, direct observation, and comprehensive documentation of Kedai AA’s operations. The findings reveal that Kedai AA implements several adaptive strategies, including gradual price adjustments, product innovation, and leveraging strong customer loyalty, efficient operational cost management, and a strategic location. The SWOT analysis further identified key internal strengths such as unique recipes and positive reputation, alongside weaknesses in financial management and limited digital technology utilization. External opportunities were identified in the growth of online food delivery platforms and government support programs for MSMEs, while threats included uncontrolled raw material price increases, declining consumer purchasing power, and intense competition. These insights led to the formulation of specific SO, WO, ST, and WT strategies aimed at maintaining profitability and enhancing business resilience in an inflationary environment.